Factors affecting consumer loan decisions of customers at Vietnamese commercial banks - Luu, Phước Vẹn; Tran , Thị Kim Khôi (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
The study was conducted to test, evaluate and measure factors that influence the consumer loan decision of individual customers at commercial banks with a sample of 190 customers in An Giang, conducted using SPSS20 software. After analyzing Cronbach’s Alpha, EFA analysis, correlation analysis and regression, the research results showed that there are 7 factors that have a positive impact on the consumer loan decision of customers, including attitudes leading to behavior, subjective norms, responsiveness, tangible means, lending policy, brand, cost and interest rate. From the research results, the author proposed a number of solutions to improve and enhance the quality of consumer loan services of banks.